The effect of work experience and rigidity on the escalation of commitments in investment decisions - Ign. Advent Susilojati; Widi Hidayat; Ake Wihadanto (Universitas Sebelas Maret, 2020)
Escalation of commitment is a form of cognitive bias that has characteristics where decision-makers tend to increase their commitment to an unfavorable investment. This study aims to prove the demographic factors of decision-makers such as work experience and rigid thinking as determinants of escalation of commitment. This research applies a 2 x 2 factorial experimental research design with a case study as an instrument of investment decision making. The participants of this experiment were regular undergraduate students as a proxy for inexperienced decision-makers and non-regular undergraduate students (executive class) as experienced proxy for decision-makers. Participants were selected using a purposive sampling technique with the adequacy criteria for General Point Average (GPA) above 3.00 and have attended and passed the Financial Management course and Theory of Decision Making course. This research uses two-ways ANOVA with a significance level of 5%. Using total 64 respondents, the results showed that work experience and rigid thinking have a significant effect on the escalation of commitment. This study also proves that the interaction between work experience and the rigidity of the decision-making mindset does not affect the level escalation of commitment.